Pastoral Care in End-of-Life: Can you be Healed when there is No Cure? - Anggun Sugiyono, Imanuel Eko; Gusti Krisna Dewi, Puri Swastika; Padmawati, Retna Siwi (International Journal of Criminology and Sociology, 2022)
When death is coming for sure, the terminally ill patients will be in sorrow. For them who do not have hope of being medically cured, do having joy and feeling serene become a possibility? Can they be healed at some point? This research aims to describe the existential experiences of the terminally illness patients’ family receiving a pastoral care. While the patients deteriorate because of illness, what type and kind of care they found most helpful? This research was a qualitative study with a phenomenology method. This paper is part of a bigger case study conducted in a Catholic hospital in Indonesia. The subjects for this research were the families of terminally ill patients. They were interviewed whether they have received pastoral care and the significance of it. The presence of pastoral care staffs and their visits were significant for the families and the patients. They feel strengthened in facing this difficult times. In particular, the spirit of the patients uplifted, they no longer feel angry with their condition and are in process of accepting the death coming their way. They found prayers as powerful resources. All the participants agreed that the pastoral care is important part for the patients’ healing. Catholic hospitals in Indonesia should be aware to provide a holistic healing. Pastoral care is one of key factors to maintain the spirit of institutions. It is the way to humanize the patients and families in their end-of-life care.